THE TEST AND LATTICEWORK DESIGNING AS ASSIGNMENT FOR PUPILS OF LEARNING EVALUATION CLASS - Aisyah, Nurul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This study describes the learning assessment be used to measure the cognitive and psychomotor domains for pupils focusing on learning evaluation class. It explores cognitive domains pupils especially when they do the assignments to design the objective test from the materials during learning before. In addition, their psychomotor domains will also be explored on the objective test and latticeworks designing, this activity is a provision of skills for prospective teachers. The task is conducted with takehome with limited time approximately 5 days. This aspect is in line with the competency-based assessment that is oriented to the level of mastery of competencies that have been targeted in the syllabus. The Assignment is used as an effort to measure the success of the learning process that has been going on, which can not be separated from 9 principles of assessment (learning assessment) listed on the regulation of the minister of education and culture of the Republic of Indonesia number 23 of 2016. This assignment has several positive impacts, including 1) the creation of a learning community – social interaction; 2) efficient, economical and practical; 3) role of lecturer, such as give some feedbacks for pupils on assessment that has a big effect on the learning of future learners; 4) the assessment based on 9 principles of learning assessment.